Parent-child play therapy effect on 10 to 12-Year-old student’ reading performance: a case of chinese male students with learning disabilities - Tian Xu (BMC Psychology, 2025)
Abstract Background Children with learning disabilities often face challenges in academic performance, particularly in reading. Parent-child play therapy has emerged as a potential intervention to address these challenges by fostering a supportive learning environment and enhancing parent-child communication. Objectives This study investigated the effectiveness of parent-child play therapy in improving reading performance among 10-12-year-old children with learning disabilities. Methodology A quasi-experimental pre-test-post-test design with a control group was employed to assess the impact of parent-child play therapy on reading performance. In 2023, the sample consisted of 100 parents of 10-12-year-olds from specialized child clinics in Shaanxi city. This pool randomly assigned 60 participants meeting inclusion criteria to the experimental group (n = 30) or the control group (n = 30). The experimental group participated in 10 sessions of 90 min of parent-child play therapy conducted weekly, while the control group did not receive any intervention. Results The MANCOVA reveals the intervention’s significant effect on combined literacy dimensions for the experimental versus control group, confirmed across all test statistics. A high partial eta squared (η² = 0.94) and power (0.99) demonstrate a strong intervention impact on reading dimensions, indicating that the intervention explains 94% of the variance in literacy outcomes, with a 99% probability of detecting the observed effects if they exist. Further ANCOVA analysis highlights specific improvements in individual literacy dimensions. The experimental group showed significantly higher adjusted posttest means in Word Reading (Adjusted Mean = 83.71, F = 10.52, p = 0.001, η² = 0.41) and Word Chain (Adjusted Mean = 88.64, F = 24.63, p = 0.001, η² = 0.62), indicating significant effects. The Rhyme Test also yielded substantial gains (Adjusted Mean = 96.92, F = 18.32, p = 0.001, η² = 0.54), alongside significant improvements in Comprehension of Text (p = 0.009, η² = 0.36) and Word Comprehension (p = 0.001, η² = 0.50). However, dimensions such as Picture Naming (p = 0.134) and Category Symbols (p = 0.058) did not show significant differences, suggesting limited intervention effects on these skills. Conclusions This study’s findings suggest that parent-child play therapy can effectively improve reading performance in children with learning disabilities. By strengthening parent-child communication skills and fostering a supportive environment, parent-child play therapy may enhance the self-confidence of children with learning disabilities, thereby facilitating significant improvements in reading skills. These findings can guide educators and therapists in designing interventions that emphasize parent-child interaction to improve literacy outcomes in educational settings. Furthermore, therapeutic settings may benefit from incorporating structured play therapy as a core strategy to target specific reading dimensions, such as Word Reading and Comprehension of Text.